Role Moderation Of Love Of Money On Accounting Students’ Ethical Behavior - Shania Savira; Arum Amalia Masyitah (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2024)
There is much debate about how much the public trusts the accounting profession to act professionally and ethically. This is due to the many important events and financial scandals involving large-scale KAP and qualified accounting professionals in fraud committed by large companies. This study aimed to analyse the moderating role of love of money on the ethical behaviour of accounting students. This article was a quantitative study with further justification. 110 questionnaires given to auditors in public accounting companies in Surabaya generated the data. PLS was employed for the statistical method. The findings showed that auditors' intention to behave ethically is positively influenced by perceived behavioural control. In addition, the findings show that although religion influences the intention to behave ethically, religiosity has no moderating effect on auditors' views of behavioural control.